2022
DOI: 10.1111/odi.14345
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the vaporization margin during CO2 laser treatment of oral leukoplakia: A survival study

Abstract: Oral leukoplakia (OL) is one of the most common potentially malignant disorder of the oral cavity (van der Waal, 2009). It was recently defined by a WHO collaborative centre as "white plaque with a questionable risk of malignancy once all other similar clinical lesions that carry no increased risk of cancer have been excluded" (Warnakulasuriya et al., 2021). It has an estimated prevalence of 4.11% (95% CI = 1. 98-6.97;Mello et al., 2018); an annual risk of malignant transformation of between approximately 2% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…25 A research study also identified small bone necrosis at a rate of 8%, delayed wound healing at a rate of 4%, and sclerotic scars at a rate of 4%. 21  Lesion resolution rates were reported in 43.2% 20 and 47.4% 18 of the patients. The disease-free survival rate during the first year was 52.9% in a study.…”
Section: Results Of Individual Studies Oral Potentially Malignant Dis...mentioning
confidence: 92%
See 4 more Smart Citations
“…25 A research study also identified small bone necrosis at a rate of 8%, delayed wound healing at a rate of 4%, and sclerotic scars at a rate of 4%. 21  Lesion resolution rates were reported in 43.2% 20 and 47.4% 18 of the patients. The disease-free survival rate during the first year was 52.9% in a study.…”
Section: Results Of Individual Studies Oral Potentially Malignant Dis...mentioning
confidence: 92%
“…19 Another study reported pain in 28.2% of the lesions. 18 Another study revealed 20% of the subjects felt pain on day 4. 22  Recurrence rates in studies were: 54.17 %, 19 52.6% after a mean of 4.8 years, 18 44.0% after a mean of 19.7 months, 21 35.1%, 20 20% after 1 month, 22 13.63 %, 25 9.1%, 23,42 and 3.3% with a nodal recurrence.…”
Section: Results Of Individual Studies Oral Potentially Malignant Dis...mentioning
confidence: 98%
See 3 more Smart Citations